دور المؤثرات السقافية في تقدير المدى الزمني للفونيم: دراسة فونولوجية حاسوبية = dawr al-mu'asirat al-siyaqiyah fi taqdir al-mada al-zamani li al-fonim: dirasah fonololojiyah hasubiyyah - Ahmed Mahmoud, Ahmed Ragheb (Department of Arabic Language and Literature, IIUM, 2012)
This study touches on the contextual effects in approximating the time range of a phoneme. This is done by tracking the time of long vowels in the samples of the study. The effects in approximating the time of the phoneme will be concluded through the analysis of the Quranic recitations by the samples which consist of reliable recitors such as Syaikh ‘Abdulla Basfar, Saikh Muhammad Ayyub, and Syaikh Masyari bin Rasyid al-‘Afasi. Among the questions the study wishes to answer: Is the approximation of the time of the phoneme a special characteristic of the recitation of the reciter and his recitation? Is it a general rule? Is it human nature which cannot be separated physiologically in the recitation of the Quran?